2013
DOI: 10.1177/0267659113517921
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nebivolol on internal mammary artery blood flow during coronary artery bypass graft surgery

Abstract: Nebivolol might represent a good choice in hypertensive patients undergoing cardiac surgery by preventing perioperative myocardial hypoperfusion which increases early morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In our study, the IMA flow was higher in the hypertensive patients than in the non-hypertensive patients, with a significant difference in flow. This high flow pattern might be related to some antihypertensive medicines that the patient was taking before surgery, as shown in other studies, as these drugs have vasodilatory effects [ 12 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our study, the IMA flow was higher in the hypertensive patients than in the non-hypertensive patients, with a significant difference in flow. This high flow pattern might be related to some antihypertensive medicines that the patient was taking before surgery, as shown in other studies, as these drugs have vasodilatory effects [ 12 ].…”
Section: Discussionmentioning
confidence: 62%
“…The left internal mammary artery is routinely used for the left anterior descending coronary artery as a part of an elective coronary artery bypass grafting procedure due to its excellent long-term patency and long-term survival in CABG patients [ 1 ]. Several previous studies have shown that a careful harvesting technique for the IMA is associated with the good flow and only occasionally topical vasodilators are used to overcome the spasm, while none of them emphasize on its relationship with different diseases and conditions [ 11 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Chan and colleagues 11 found that those patients who were discharged and prescribed beta-blockers after cardiac surgery exhibited a substantially lower rate of death at 1 year. Sarikaya and colleagues 15 suggest that nebivolol might be considered a good choice in hypertensive patients undergoing cardiac surgery, given its prevention of perioperative myocardial hypoperfusion, which increases early morbidity and mortality. Bayar and colleagues 16 suggest that nebivolol may be safer and preferable to diminish graft spasm in patients undergoing CABG surgery because of the NO-mediated vasodilation effect.…”
Section: Discussionmentioning
confidence: 99%
“…The primary limitation of our study was that there were no flow measurements made after applying the papaverin. In a recently published paper, Sarikaya et al [25] reported that when compared with other antihypertensive drugs, pretreatment with nebivolol increases the IMA GFF even after papaverine usage. The second limitation was that the medication was only used for a short time in the study groups, Although there was a statistical difference in our study, longer times of pretreatment will undoubtfully strengthen our results.…”
Section: Discussionmentioning
confidence: 99%